2005
DOI: 10.1063/1.1886261
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of gas-phase molybdenum nanoclusters: A transmission electron microscopy study

Abstract: In this paper we study structural aspects of molybdenum clusters by transmission electron microscopy. The deposited clusters with sizes 4nm or larger show a body-centered crystal (bcc) structure. The clusters are self-assembled from smaller structural units and form cuboids with a typical size of 4nm or larger. With reducing cluster size, the face-centered crystal (fcc) structure appears due to dominance of surface energy minimization, while self-assembly into large cuboids with sizes up to 30nm is still obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…Compared to the nanoclusters by sputtering deposition [16][17][18], the bigger size of the regular faceted Cu particles can be attributed to the fact that the thin films can provide sufficient atoms for their continuous growth through the diffusion along grain boundaries. As demonstrated by Hwang et al [4], the sizes of faceted Cu particles may be changed by adjusting the film thickness and annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the nanoclusters by sputtering deposition [16][17][18], the bigger size of the regular faceted Cu particles can be attributed to the fact that the thin films can provide sufficient atoms for their continuous growth through the diffusion along grain boundaries. As demonstrated by Hwang et al [4], the sizes of faceted Cu particles may be changed by adjusting the film thickness and annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many experiments and computer simulation are performed on nanosized clusters and submicron-scale metal pillars and particles to investigate the intrinsic properties of materials [12][13][14][15][16][17][18]. The results demonstrated that their physical, chemical and mechanical properties apparently differ from those of corresponding bulk ones.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control surface feature on this length scale is essential in future nanotechnology. Deposition of nanoparticles has emerged as an important technique to assemble nanostructures [7][8][9][10][11][12][13][14]. The main challenges are to produce size-selected nanoparticles, and to control the interaction with the substrate so that the original nanoparticle properties are being preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for magnetic nanoparticles [3,4,[11][12][13][14][15][16][17][18][19][20][21][22] magnetic anisotropy generates magnetic easy axes with an energy barrier separating different orientations of the magnetic moment. Without an external field the magnetic moment is in a blocked state, unless thermal activation is able to overcome the anisotropy energy barrier and induce moment flipping in between easy directions (super-paramagnetism).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation